Case Study Research, Philosophical Position and Theory Building: A Methodological Discussion - Bhatta, Thakur Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2018)
Case study research though increasingly popular in social sciences for positivist and intrepretivist research, a kind of confusion is prevalent when it is used ignoring its philosophical position. Arguably, the case study research is considered more appropriate for qualitative research because of its foremost strength ˗ the in-depth study of complex issues. This paper, drawing from the literature, discusses the philosophical position of case study research and argues that qualitative case study research is appropriate for theory building. For theory building, this paper follows the inductive approach guided by qualitative research paradigm and argues that it is not appropriate to assess theory building from the perspective of quantitative research. Very similar to other research methods, it is natural that the case study research has certain challenges; however, most of the challenges and misunderstandings overlap causing difficulty to understand the role of case study research. Hence, this paper aims to contribute to the understandings of the challenges and misunderstandings associated with the theory building from case study research. This paper argues that most of the challenges associated with theory building from case study can be addressed employing appropriate research strategies particularly clear understanding of philosophical stance and selection of appropriate case. The misunderstandings, on the other hand, are arisen due to the differences in the researcher’s perspectives particularly positivistic thinking of them rather than the shortcomings inherent in the qualitative case study research design.